Pharmacologic Management of Hypertensive Disorders of Pregnancy and Postpartum Hypertension: Current Evidence and Clinical Implications - Tona , Azwar Iwan (Journal of Society Medicine, 2026)
Hypertensive disorders of pregnancy remain a major cause of preventable maternal morbidity and mortality worldwide, encompassing a spectrum of conditions from chronic and gestational hypertension to severe hypertensive crises associated with preeclampsia and eclampsia. Severe elevations in blood pressure (systolic ≥160 mmHg and/or diastolic ≥110 mmHg) markedly increase the risk of stroke, cardiovascular complications, and adverse perinatal outcomes, underscoring the need for prompt and appropriate pharmacological intervention. This review synthesizes contemporary evidence regarding treatment thresholds, target blood pressure goals, and the comparative efficacy and safety of commonly used antihypertensive agents, including labetalol, nifedipine, hydralazine, and methyldopa, in both antepartum and postpartum settings. Emerging randomized trials and meta-analytic data supporting earlier intervention in non-severe chronic hypertension are discussed, along with clinical considerations unique to the postpartum period, during which blood pressure instability and stroke risk remain elevated. Therapeutic decision-making must balance maternal cardiovascular protection with fetal and neonatal safety, considering placental drug transfer and the relative scarcity of long-term outcome data. An individualized, evidence-based, and multidisciplinary approach throughout the antepartum and postpartum continuum is essential to prevent severe hypertension, minimize end-organ injury, and improve immediate and long-term maternal cardiovascular outcomes.